The Impact of Underground Longwall Mining on Prime Agricultural Land: A Review and Research Agenda. (20th August 2014) - Lechner, Alex Mark; Baumgartl, Thomas; Matthew, Phil; Glenn, Vanessa
Abstract: Coal mining and agriculture have repeatedly come into conflict when they co‐occur. Although seemingly benign when compared with surface mining, underground coal extraction techniques (including longwall mining) cause subsidence of agricultural land and loss of productivity. Despite growing concerns for global food security and increasing demand for coal resources, there is little peer‐reviewed literature on the impacts of longwall mining in prime agricultural areas. In this paper, we examined the present knowledge of subsidence impacts of longwall mining on agriculture and how this may be interpreted for specific locations such as Australia. The review found that subsidence affects soil properties, hydrology and topography. The main impacts on agriculture are altered soil and groundwater hydrology, modified topography associated with increased erosion or waterlogging risk, and zones of compaction or cracking that cause soil physical and chemical changes. Agricultural productivity is also reduced through altering the types of farming practices that are suited to subsided non‐uniform landscapes, decreasing farming efficiency through increasing paddock heterogeneity and decreasing ease of workability. There is a need to consider these multiple impacts under local conditions, with particular regard to the interaction of mine subsidence‐associated disturbances with farming practices. We conclude by describing future research directions required for Australia and other countries outside of the USA—where most of the research has been conducted. Australia has unique soil and climatic conditions making extrapolation of studies from the USA on subsidence impacts and mitigation problematic. Copyright © 2014 John Wiley & Sons, Ltd.